Serum Dehydroepiandrosterone (DHEA) and DHEA Sulfate Are Negatively Correlated with Serum Interleukin-6 (IL-6), and DHEA Inhibits IL-6 Secretion from Mononuclear Cells in Man in Vitro: Possible Link between Endocrinosenescence and Immunosenescence - Straub, R. H.; Konecna, L.; Hrach, S.; Rothe, G.; Kreutz, M.; Schölmerich, J.; Falk, W.; Lang, B. (The journal of clinical endocrinology and metabolism, 1998)
Interleukin-6 (IL-6) is one of the pathogenetic elements in inflammatory and age-related diseases such as rheumatoid arthritis, osteoporosis, atherosclerosis, and late-onset B cell neoplasia. In these diseases or during aging, the decrease in production of sex hormones such as dehydroepiandrosterone (DHEA) is thought to play an important role in IL-6-mediated pathogenetic effects in mice. In humans, we investigated the correlation of serum levels of DHEA, DHEA sulfate (DHEAS), or androstenedione (ASD) and IL-6, tumor necrosis factor-α, or IL-2 with age in 120 female and male healthy subjects (15–75 yr of age). Serum DHEA, DHEAS, and ASD levels significantly decreased with age (all P < 0.001), whereas serum IL-6 levels significantly increased with age (P < 0.001). DHEA/DHEAS and IL-6 (but not tumor necrosis factor-α or IL-2) were inversely correlated (all patients: r = −0.242/−0.312; P = 0.010/0.001). In female and male subjects, DHEA and ASD concentration dependently inhibited IL-6 production from peripheral blood mononuclear cells (P = 0.001). The concentration-response curve for DHEA was U shaped (maximal effective concentration, 1–5 × 10−8 mol/L), which may be the optimal range for immunomodulation. In summary, the data indicate a functional link between DHEA or ASD and IL-6. It is concluded that the increase in IL-6 production during the process of aging might be due to diminished DHEA and ASD secretion. Immunosenescence may be directly related to endocrinosenescence, which, in turn, may be a significant cofactor for the manifestation of inflammatory and age-related diseases.